Peran Ekonomi Islam dalam Mengatasi Permasalahan Ekonomi Global di Pakistan - Muhammad Nurjati; Hamam Mishbakhuzzein; Dea Safitri; Mohammad Ridwan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Global economic problems such as inflation, unemployment, financial crises, economic inequality, and increasing foreign debt are challenges faced by many countries, including Pakistan. As a country with a Muslim majority population, Pakistan has the potential to implement an Islamic economic system as a solution to overcome these various economic problems. This study aims to determine the condition of global economic problems in Pakistan, understand the concept of Islamic economics in addressing economic problems, and analyze the role of Islamic economics in helping overcome global economic problems in Pakistan. The research method used is qualitative research with a descriptive approach through library research. Data were obtained from various sources such as scientific journals, books, articles, and relevant documents, then analyzed using qualitative descriptive analysis techniques. The results of the study indicate that global economic problems faced by Pakistan are influenced by dependence on foreign debt and investment, energy and environmental crises, political instability, limited green financing, economic policy uncertainty, and global geopolitical risks. Islamic economics plays a role in overcoming these problems by implementing a riba-free financial system, maintaining the stability of the value of money, encouraging productive financing, realizing justice and income equality, avoiding excessive speculation, and increasing transparency and responsibility in economic activities. By applying these Sharia principles, Islamic economics can be an alternative solution to creating a more just, stable, and sustainable economic system for the people of Pakistan.